2013
DOI: 10.1371/journal.pone.0075961
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Thrombomodulin Protects Mice against Histone-Induced Lethal Thromboembolism

Abstract: IntroductionRecent studies have shown that histones, the chief protein component of chromatin, are released into the extracellular space during sepsis, trauma, and ischemia-reperfusion injury, and act as major mediators of the death of an organism. This study was designed to elucidate the cellular and molecular basis of histone-induced lethality and to assess the protective effects of recombinant thrombomodulin (rTM). rTM has been approved for the treatment of disseminated intravascular coagulation (DIC) in Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
158
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(161 citation statements)
references
References 42 publications
3
158
0
Order By: Relevance
“…Elevated histone‐degrading activated protein C (APC) levels are associated with better outcomes in sepsis115, 149 and trauma patients137; APC therapy is being evaluated for treatment of sepsis150 and pancreatitis 151. The effects of histones and NETs on the coagulation cascade can be overcome by therapy with thrombomodulin121 or tissue plasminogen activator (tPA),143 but the clot‐stabilizing effects of DNA in NETs must be overcome, which is well illustrated by the finding that DNAse therapy in addition to tPA is more effective than either therapy alone 152…”
Section: Therapeutic Strategies For Histone Detoxification In Pathologymentioning
confidence: 99%
“…Elevated histone‐degrading activated protein C (APC) levels are associated with better outcomes in sepsis115, 149 and trauma patients137; APC therapy is being evaluated for treatment of sepsis150 and pancreatitis 151. The effects of histones and NETs on the coagulation cascade can be overcome by therapy with thrombomodulin121 or tissue plasminogen activator (tPA),143 but the clot‐stabilizing effects of DNA in NETs must be overcome, which is well illustrated by the finding that DNAse therapy in addition to tPA is more effective than either therapy alone 152…”
Section: Therapeutic Strategies For Histone Detoxification In Pathologymentioning
confidence: 99%
“…These events have been directly linked to lung injury after trauma or transfusions [22,[97][98][99]. PAD4 and neutrophils have been shown to be critical for deep-vein thrombosis in mice [100].…”
Section: Platelet Activation and Thrombin Generation By Histonesmentioning
confidence: 99%
“…PAD4 and neutrophils have been shown to be critical for deep-vein thrombosis in mice [100]. IIIa [92,97,99]. Heparin has been shown to prevent binding of histones to platelets and protect against thrombocytopenia, tissue injury and death caused by histone infusion [92].…”
Section: Platelet Activation and Thrombin Generation By Histonesmentioning
confidence: 99%
“…Indeed, increased levels of circulating histones and nucleosomes have been found in patients with a range of inflammatory conditions, including sepsis, [1][2][3] traumatic injury and surgery, [3][4][5][6] cerebral stroke, 7 systemic lupus erythematosus, 8 and cancer. 9,10 In 2009, Xu et al 11 demonstrated that histones released by macrophages upon inflammatory challenge were cytotoxic to endothelial cells in vitro.…”
Section: Introductionmentioning
confidence: 99%